ANALISIS RESIKO CEMARAN DEBU (TSP) AKIBAT ASAP PABRIK TERHADAP PEKERJA DAN MASYARAKAT SEKITAR (Studi Kasus : PT. Inti General Yaja Steel, Semarang) - Yanida Ratnasari (Jurnal Teknik Lingkungan, 2013)
The stack of the factory production process can produce dust pollutants (TSP) that dangerous and  carcinogenic. PT. Inti General Yaja Steel Semarang is a kind of steel smelting industry that took out the impurities in dust that spread to the residential area around so that residents can affect the health of inhalation in humans. This research was aimed at analysing the risk from related pollutant for people who live or work in the vicinity of industries. This research consists of four steps i.e hazard identifications, exposure assessment, toxicity assessment, and risk characterization. Four locations had been selected for field sampling. Hazard identifications to dust (TSP) concentration was mirrored to ambient air standard that maximal concentration for the TSP is 230 μg/m3. On exposure assessment the TSP concentration in PT.IGYS, Ngepos II street, Sugriwo II street and Krapyak complex exceed ambient air standard (SK. Gub. Jateng No. 08/2001). Toxicity assessment revealed that TSP intake in all place was safe since the calculated intake were still under maximal intake 0,0452 mg/kg.day. Based on risk characterization result, it can be concluded that level of risk in all places was less than unity (<1) so it implies that in those area was safe for daily activities in specified time with respect to dust (TSP). However the relative high risk was pointed out to the Krapyak complex and the lowest risk was in Ngepos II street.